"Dreaming While Awake": The Evolution of the Concept of Hallucination in the Nineteenth Century - Shane McCorristine (University of Edinburgh, 2006)
This paper will show that the rationalist theory of "spectral illusions" which discounted the objective reality of ghost-seeing, was challenged during the rise of the spiritualist faith, which drew a huge amount of attention from the scientific and artistic community to the psychogenesis of hallucinations and the rich research possibilities to be found in studying the fallacies of perception. Coming in the wake of the establishment of spiritualism, it will be seen that the Society for Psychical Research proposed that a certain number of hallucinations were "veridical" in that they corresponded to a real and verifiable event in the world - such as the death of a loved one - and could be apprehended telepathically. Thus, hallucinations represent a key concept in nineteenth-century debates surrounding notions of psychological truth, spiritual revelation, and the vagaries of the human imagination.